(untitled) (Per Musi, 2023)
This article aims to discuss the instrumentality of water in the repertoire for percussion, using the performance of the work Water Music (2004) by Chinese composer Tan Dun (1957) as a case study. Rooted in my own artistic practice (as percussionist, improviser and composer) in the performance of the work as the core of research process, this investigation also combined methods and theoretical perspectives from the fields of auto- and performative-ethnography (Wong 2008), in addition to semi-structured interviews with other percussionists specialists in Tan Dun’s water percussion works. Starting with an overview on water’s integration into Western art music and its dynamic connection with percussion, this investigation intended to reveal, from the perspective of a percussionist, the intricate performative process involved in Tan Dun’s Water Music. This investigation underscored the presence of a unique performance path, shaped by singular performative demands, in addition to creative and experimental artistic practices.